FAKTOR YANG MEMPENGARUHI FERTILITAS DI JAWA BARAT: STUDI LITERATUR - Rizal Ahmad Rasyad; Mirna Nur Alia Abdullah (Yayasan Literasi Sains Indonesia, 2024)
Birth or fertility has become the cause of issues in Indonesia. One of the provinces, West Java, contributes significantly to the country's population. In 2018, the population was recorded at 48,683,861 people, and it increased to 49,935,858 people in 2020. The population is distributed across various regions in West Java. One of the causes of the high population is birth or fertility. Fertility is a term in demography used to identify the number of children a woman can bear. The research method used is a literature study involving the analysis of various journal sources or articles. The aim of this research is to determine the factors influencing fertility in West Java. The results found factors influencing fertility including marriage factors, migrant fertility factors, education factors, socio-economic level factors (income), and environmental factors. This research illustrates the factors influencing fertility in West Java. From the results of the research, it can be concluded that there are several factors contributing to the high fertility rate in the region.